Telaah Kritis Realisasi Belanja Daerah Provinsi Sulawesi Selatan Tahun Anggaran 2020- 2021 Dari Prespektif Quality Spending - Sari, Yunita Ratna (Universitas Cenderawasih, 2024)
APBD has an important role in carrying out local government activities. Regional spending is a crucial part of the APBD structure because it will show the the ability of local governments to manage regional finances, whether they can be effective, efficient and accountable. This study uses the method of literature study with descriptive analysis. Secondary data as the main data source in this study. Secondary data in this research includes journals, national surveys and government agency data publications. The results of the study show that the realization of regional spending in the province of South Sulawesi cannot be categorized as quality regional spending because there has been a decrease in the realization of regional spending from 2.11 trillion in 2022 to 3.10 trillion in 2021.